2010
DOI: 10.4329/wjr.v2.i7.283
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis secondary to intramural duodenal hematoma: Case report and literature review

Abstract: Nontraumatic intramural duodenal hematoma (IDH) is rare disease and it is generally related to coagulation abnormalities. Reports of nontraumatic IDH associated with pancreatic disease are relatively rare, and various conditions including acute or chronic pancreatitis are thought to be associated with nontraumatic IDH. However, the association between IDH and acute pancreatitis remains unknown. We report the case of a 45-year-old man who presented with vomiting and right hypochondrial pain. He had no medical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Very few (<30) cases of IDH after biopsy or sclerotherapy have been reported in the literature to our knowledge [ 9 ]. Most of these patients with IDH after hemostatic therapy had underlying coagulopathy, thrombocytopenia and/or liver cirrhosis [ 4 , 7 , 9 12 ]. Dibra et al [ 13 ] however reported a case of IDH after submucosal epinephrine therapy for duodenal bleeding ulcer in a patient without apparent underlying disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few (<30) cases of IDH after biopsy or sclerotherapy have been reported in the literature to our knowledge [ 9 ]. Most of these patients with IDH after hemostatic therapy had underlying coagulopathy, thrombocytopenia and/or liver cirrhosis [ 4 , 7 , 9 12 ]. Dibra et al [ 13 ] however reported a case of IDH after submucosal epinephrine therapy for duodenal bleeding ulcer in a patient without apparent underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient has a similar associated acute pancreatitis but without any known underlying coagulopathy or cirrhosis. The development of acute pancreatitis in cases of IDH has been attributed to hematoma compression of the pancreatic duct and obstruction of duodenal papilla [ 12 , 14 ]. Other explanations have included the possibility of pancreatic enzyme release during acute or chronic pancreatitis, causing vascular destruction thereby leading hematoma formation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Causes of the development of acute pancreatitis in patients with IDH include duodenal papilla obstruction and pancreatic duct compression (13). Obstructive acute pancreatitis is another complication resulting from impaired pancreatic enzyme secretion due to obstruction of the duodenal papilla.…”
Section: Discussionmentioning
confidence: 99%
“…Similar shift can be observed in IDH cases, as shown in Table 1 , large case series and reports of IDH discussed 236 cases before the year 2000 and 157 (67%) cases were managed by operative intervention. After 2000, there are 46 reported cases of IDH with 10 (22%) of them required drainage [2] , [11] , [12] , [13] , [14] , [15] .…”
Section: Discussionmentioning
confidence: 99%